BIBLIOMETRIC ANALYSIS USING VOSVIEWER ON LEARNING AGILITY RESEARCH TRENDS IN GOOGLE SCHOLAR - Wayan Arya Paramarta; I Wayan Gede Supartha, I Gusti Ayu Manuati Dewi, Ida Bagus Ketut Surya (Adisam Publisher, 2024)
Bibliometric analysis is mapping research trends using metadata processing from Google Scholar. The aim is to find out research trends about learning agility. The research was carried out by searching the Google Scholar database with the keywords learning agility and the maximum number of results was 1000 journals as a sample. Retrieval of metadata using the Publish or Perish application version 8.94. The data from Publish or Perish is then analyzed descriptively based on the year the publication was published, publisher name, researcher productivity, and journal ranking. To obtain an accurate map of research progress, Publish or Perish data is exported to Exel CSV and Result as RIS file formats. CSV data was made into a pivot table and RIS data was analyzed using the VOSviewer application. The research results show that the number of research publications in 2000-2023 has fluctuated and most were published in Emerald. The most productive foreign researcher in publishing research results is Kenneth P. De Meuse with 12 articles. Through VOSviewer visualization, it shows that the learning agility research development map is divided into 5 clusters. Cluster 1 consists of 20 items, cluster 2 consists of 15 items, cluster 3 consists of 14 items, cluster 4 consists of 9 items and cluster 5 consists of 8 items with the most research covering effect, strategic agility, concept, skill and work.